Training on Enhancing Women's Role in Supporting Household Economy - Nurhayati, Nurhayati; Jakaria, Jakaria; Aina Zahra Parinduri (International Journal of Community Service Implementation, 2023)
Women's contribution to family income is increasingly necessary, especially during the current economic crisis. Women's limited access to market opportunities is shown by their low participation in formal businesses. Most women still work in the informal sector and in jobs that do not use sophisticated equipment and technology. This work usually does not provide adequate social and legal protection and welfare guarantees, in addition to unhealthy working conditions and of course low income levels. Azalea MSMEs are currently almost mostly women entrepreneurs, expected to support the household economy. Therefore, this PKM activity aims to provide training to be able to increase the role of women (community and Azalea MSMEs) in supporting the household economy, it is hoped that women can have financial independence